2010
DOI: 10.1016/j.surfcoat.2010.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Industrial-scale deposition of highly adherent CNx films on steel substrates

Abstract: Highly adherent carbon nitride (CN x ) films were deposited using a novel pretreatment with two high power impulse magnetron sputtering (HIPIMS) power supplies in a master-slave configuration: one to establish the discharge and one to produce a pulsed substrate bias. During the pretreatment, SKF3 (AISI 52100) steel substrates were pulse-biased in the environment of a HIPIMS Cr plasma in order to sputter clean the surface and to implant Cr metal ions. Subsequently, CN x films were prepared at room temperature b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 45 publications
(34 reference statements)
1
35
0
Order By: Relevance
“…steel) [15]. But Broitman et al reported that CNx films deposited by reactive magnetron sputtering on metallic biomaterials exhibit good tribological properties and improved adhesion on metallic substrates [16][17][18]. Moreover the low coefficient of friction (COF) of CNx films has the potential to cause lower wear against polymeric materials such as ultra-high molecular weight polyethylene (UHMWPE) in human serum conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…steel) [15]. But Broitman et al reported that CNx films deposited by reactive magnetron sputtering on metallic biomaterials exhibit good tribological properties and improved adhesion on metallic substrates [16][17][18]. Moreover the low coefficient of friction (COF) of CNx films has the potential to cause lower wear against polymeric materials such as ultra-high molecular weight polyethylene (UHMWPE) in human serum conditions [19].…”
Section: Introductionmentioning
confidence: 99%
“…Thick a-CN X film deposition on steel substrate by magnetron sputtering process is limited due to poor adhesion between the film and substrate as well as because of high compressive stress which can be built up inside the film during the deposition process [27]. Wang et al [28] reported that after a certain critical bias voltage (-150 V), the adhesion between the film and substrate decreases with increasing bias voltage.…”
Section: State Of the Art Of A-cn X Materialsmentioning
confidence: 99%
“…Another practice is to apply some kind of additive layer by means of sputtering the metal target material between the film and substrate as a bonding agent. Broitman et al [27] demonstrated that the high energy chromium (Cr) plasma etching in HiPIMS can substantially clean the oxide and other contaminants from the steel substrate surface and thus can enhance the adhesion. They also showed that a thin sublayer of Cr (100 nm) as well as amorphous transition layer deposited by HiPIMS in master-slave configuration can further increase the adhesion.…”
Section: State Of the Art Of A-cn X Materialsmentioning
confidence: 99%
“…These amorphous films are a mix of sp 3 tetrahedral bonding (like in single-crystal diamonds) and sp 2 trigonal bonding (like in single-crystal graphite), and usually deposited by physical or chemical vapor deposition techniques 14 . Since Bhushan published the first nanotribological study of amorphous carbon films using an atomic force microscope (AFM) 15 , there have been many studies about the nanotribological properties of carbon-based coatings, as it has been reviewed for dry and lubricated conditions [16][17][18][19][20][21][22] . We can observe that for dry tests (Figure 8a), the friction coefficient decreases with the increase of the applied load from 10 µN to 100 µN, and stays constant when increasing from 100 µN to 1000 µN.…”
Section: Wear Ratio and Wear Ratementioning
confidence: 99%